California School Nurses Report on Oral Health Needs of Children and Willingness to Conduct Annual Oral Health Screenings - Caitlin Neapole; Vinodh Bhoopathi (Taylor & Francis Group, 2024)
Introduction The California Department of Public Health (CDPH) conducted an oral health assessment of third-grade children in 2018-2019, showing that dental caries still affected most children in this age group. When trained, School Nurses (SNs) can do regular oral health screenings, educate children on the importance of oral health, and refer children with dental needs to a dentist.Objectives To determine if SNs 1) witness children complain of pain in mouth and teeth, 2) see children with root tips, and 3) are willing to conduct annual oral health screenings.Methods A 23-item survey was sent out to active SN members of the California School Nurses Organization in this cross-sectional study. Univariate and bivariate analyses were conducted.Results Almost 81% reported that the children they serve complained of dental pain, and 46% reported seeing children with root tips. Approximately 64% indicated their willingness to conduct annual oral health screenings. SNs with master's degrees and above were more likely to witness complaints of dental pain (p = 0.006) and see children with root tips (p = 0.002).Conclusions A high proportion of SNs who participated in this study witnessed complaints about dental pain from school children where they serve and seeing children with retained root tips, suggesting that the children in their schools may have high unmet dental needs. The majority of the responding SNs were positive about conducting oral health screenings. SNs, when trained, can be a great resource in developing and implementing school-linked dental programs in California schools.